A study on the development of Xitang's homestay tourism from the perspective of consumer purchase behaviour. (18th August 2018) - Qu, Jiayi
Abstract: With the continuous improvement of people's living standards, tourism, especially the accommodation industry, is developing rapidly. As an important part of non-standard accommodation industry, it has developed rapidly in recent years, especially by the consumption of the new youth generation. Consumer buying behaviour is an important factor affecting the development of the house. This paper studies the status of Xi tang's residential development from the angle of "consumption purchase behaviour" and passes the local residence to Xi tang. On the basis of the current status of the development of Xi tang's residence and the theory of consumer purchase behaviour, the residents' motivation of accommodation is investigated, including the adjustment of pressure and relaxation for most tourists to choose the consumption motivation of the Xitang lodging. From the aspects of relevant policies, service quality and living environment, the corresponding countermeasures and suggestions are put forward.